ChemInform Abstract: A Challenging Heck Reaction of Maleimides. Issue 45 (November 2015) - Lim, Li Hui; Zhou, Jianrong
Abstract An efficient Heck method for the arylation of maleimides which easily undergo hydrolysis is presented.